2019
DOI: 10.1111/gbb.12601
|View full text |Cite
|
Sign up to set email alerts
|

Variability in nicotine conditioned place preference and stress‐induced reinstatement in mice: Effects of sex, initial chamber preference, and guanfacine

Abstract: Relapse to smoking occurs at higher rates in women compared with men, especially when triggered by stress. Studies suggest that sex‐specific interactions between nicotine reward and stress contribute to these sex differences. Accordingly, novel treatment options targeting stress pathways, such as guanfacine, an α2‐adrenergic receptor agonist, may provide sex‐sensitive therapeutic effects. Preclinical studies are critical for elucidating neurobiological mechanisms of stress‐induced relapse and potential therapi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 106 publications
(260 reference statements)
1
11
0
Order By: Relevance
“…The VTA or NAc shell proteomes were examined after subchronic nicotine administration and after withdrawal from chronic nicotine administration as shown by the workflow depicted in Figure 1. Sub-chronic nicotine was administered at doses and on a schedule that induces CPP in C3H/HeJ mice (Lee et al, 2020). Chronic nicotine was administered to C57BL/6J mice through drinking water for 21 days, followed by 24 h of normal drinking water administration prior to tissue collection, at which point mice can exhibit signs of withdrawal (Jackson and Imad Damaj, 2013;Damaj et al, 2003).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The VTA or NAc shell proteomes were examined after subchronic nicotine administration and after withdrawal from chronic nicotine administration as shown by the workflow depicted in Figure 1. Sub-chronic nicotine was administered at doses and on a schedule that induces CPP in C3H/HeJ mice (Lee et al, 2020). Chronic nicotine was administered to C57BL/6J mice through drinking water for 21 days, followed by 24 h of normal drinking water administration prior to tissue collection, at which point mice can exhibit signs of withdrawal (Jackson and Imad Damaj, 2013;Damaj et al, 2003).…”
Section: Resultsmentioning
confidence: 99%
“…Different doses of nicotine were used to produce similar levels of nicotine reward in male and female mice, accounting for sex differences in nicotine response and sensitivity, including pharmacokinetic differences in nicotine absorption and metabolism (Kota et al, 2007(Kota et al, , 2008Lenoir et al, 2015;Pogun and Yararbas, 2009). We have previously demonstrated that the specific doses used in this study produce CPP in C3H/HeJ mice (Lee et al, 2020). The nicotine group received alternating injections of nicotine and saline on days 5-10, while the control group received saline on all days while alternating chambers on days 5-10.…”
Section: Sub-chronic Nicotine Exposurementioning
confidence: 90%
See 1 more Smart Citation
“…In the pre-test stage, mice were placed in the central chamber and given 20 min of free access to all chambers. Drug-naive mice that spent .65% of their time in one of the two conditioning chambers were removed from the study and the remaining mice were counter-balanced, similar to previously published methods (Neugebauer et al, 2011;Einstein et al, 2013;Lee et al, 2020). Eight males and five females were excluded.…”
Section: Cpp Assaysmentioning
confidence: 99%
“…Stress can also lead to reinstatement of drug‐seeking behavior, an effect observed equally in male and female mice. However, Lee et al show that the ability of the drug guanfacine to prevent stress‐induced reinstatement of nicotine‐seeking behavior in a conditioned place preference test depends on a novel interaction between sex and individual animals' preferred test chamber at baseline, suggesting a role for sex‐dependent context processing in the likelihood of substance abuse treatments being successful. Other aspects of addiction—such as substance type, age of initiation, and abuse trajectories—have clear sex and gender differences, suggesting a need for sex‐specific evaluation of addiction mechanisms.…”
mentioning
confidence: 99%